Western Indian Ocean and Impacts of SDG14: Life Below Water - Vimala Dheekshanya V.; Devesh A.; Prashanth Arjun G.K (International Journal of Marine Life, 2025)
The SDGs outline a sustainable and inclusive global future. This paper discusses progress toward SDG 14 within the WIO, emphasizing four targets that were set for achievement by 2020. Given that current methods of evaluation of policy-informing lack precision, in this region, little headway has been made toward meeting the set targets, and the attainment of SDG 14 by 2030 does not seem possible. SDG 14.2 and 14.5: Moving at a Snail’s Pace for Marine Conservation. Some countries protected only 10 percent of the more marine areas. In fisheries management, progress toward SDG 14.4 (reducing harmful subsidies) and SDG 14.6, combating illegal, unreported, and unregulated (IUU) fishing) is yielding positive, though modest, results. While the socio-economic and governance structures across the WIO (Western Indian Ocean) region vary, the potential for restoring ecological health remains high. To overcome existing challenges and achieve SDG 14, it will be crucial to strengthen monitoring systems, promote integrated governance, invest in capacity building, and foster knowledge sharing. The region will gain social, economic, and environmental advantages from better SDG implementation.
Keywords: Marine conservation; Western Indian Ocean (WIO); area-based management tools; fisheries management; marine protected areas; monitoring and reporting systems; ocean governance; policy and decision-making; regional advancements; sustainable resource management